IDENTIFICATION OF ETHNOSCIENCE IN THE MANGROVE FOREST OF SEPULU AS A SOURCE FOR LEARNING SCIENCE IN JUNIOR HIGH SCHOOLS - Mochammad Yasir; Mochammad Ahied; Sofiatun Sofiatun; Eva Agustintias (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2026)
This study aims to identify the ethnoscience found in the mangrove forest of Sepulu which can be used as a source of learning natural sciences for junior high schools. The time of research was in March at the Sepulu mangrove ecotourism, Bangkalan. Methods of data collection using the method of observation, interviews and documentation. Data analysis techniques use data reduction, data presentation, conclusions and verification. There is data triangulation using the triangulation method by matching the interview results with the observation sheet. The results of the data findings were then verified by the SMP science teacher. The results of the study show that: 1) the results of ethnoscientific studies are visible in ecosystems, community techniques in caring for and maintaining the Sepulu mangrove forests, conservation and rehabilitation carried out as well as processed products from mangrove forests produced by local communities. 2) the results of the ethnoscience study are connected and closely related to science concept material for junior high school grades 7 8 independent curricula, namely material for classification of living things, ecosystems, ecology and biodiversity, earth and the solar system, plant structure, interactions in ecosystems, conservation in grade 7 and materials for food and digestive systems for grade 8. These results indicate that the mangrove forest of Sepulu can be used as a source of learning natural sciences for junior high school.